Anti‐inflammatory and protective effects of 2‐methacryloyloxyethyl phosphorylcholine polymer on oral epithelial cells. Issue 2 (6th May 2014) - Yumoto, Hiromichi; Hirota, Katsuhiko; Hirao, Kouji; Miyazaki, Tsuyoshi; Yamamoto, Nobuyuki; Miyamoto, Koji; Murakami, Keiji; Fujiwara, Natsumi; Matsuo, Takashi; Miyake, Yoichiro
Abstract Periodontitis is a chronic inflammatory disease initiated by a microbial biofilm formed in the periodontal pocket. Gingival epithelium plays important roles as the first physical barrier to bacterial invasion and in orchestrating the innate immune reaction via toll‐like receptors (TLRs), which recognize various bacterial products, and maintaining its function. Newly developed oral care products to inhibit bacterial adherence, subsequent inflammatory reaction and protect the gingival epithelium are expected. We previously reported that 2‐methacryloyloxyethyl phosphorylcholine (MPC)‐polymer coating decreased bacterial adhesion to human oral keratinocytes, RT‐7, and mouth‐rinsing with MPC‐polymer inhibited the increase of oral bacteria. In this study, regarding the possibility of MPC‐polymer application for preventing the adherence of periodontal pathogen, subsequent inflammatory reaction and protection of gingival epithelium, we examined the effects of MPC‐polymer on the adherence of Porphyromonas gingivalis, major periodontitis‐related pathogen, and TLR2 ligand to RT‐7 and subsequent interleukin (IL)−8 production. MPC‐polymer treatment significantly reduced P. gingivalis adherence by 44% and TLR2‐mediated IL‐8 production by blocking the binding of its specific‐ligand in a concentration‐dependent manner. Furthermore, MPC‐polymer pretreatment protected RT‐7 from injury by chemical irritants, cetylpyridinium chloride. These findings suggest that MPC‐polymer is potentially useful for oral care to prevent oral infection and to maintain oral epithelial function. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 555–563, 2015.